Synthesis, characterization, and electrocatalytic hydrogen evolution of transition metal Schiff-base calixpyrrole complexes with pendant hydrogen bond donors - Trowbridge, Logan Jacob (Kansas State University, 2024)
Three novel calixpyrrole complexes with pendant hydrogen bond donors were synthesized via the condensation of 5,5’-diformyl-2,2’-diphenyldipyrromethane and an aniline precursor. Single crystal X-ray diffraction revealed that these complexes displayed distorted square planar geometries, and significantly the pendant groups remained uncoordinated from the metal. Electrochemical studies, along with density functional theory (DFT) calculations, indicated that the ligand exhibited redox non-innocence as evidenced experimentally by similar irreversible oxidations in both the ligands and complexes. Electrochemical analysis in the presence of p-toluenesulfonic acid generated an irreversible reduction about 400-500 mV more positive than the background reduction by the glassy carbon electrode, indicative of electrocatalytic hydrogen evolution. All the complexes exhibited similar catalytic waves which persisted after rinse tests signifying the generation of an electrode-adsorbed catalyst which was stable under catalytic conditions. A square planar Ni(II) complex, Ni(DPMDA) (DPMDA=2,2’-((diphenylmethylene)bis(1H-pyrrole-5,2-diyl))bis-(methaneylylidene))bis(azaneylylidene))dianiline), of the previously reported calixpyrrole ligand of was synthesized and analyzed for electrocatalytic hydrogen evolution in the presence of anilinium tetrafluoroborate. It was found that under catalytic conditions a heterogeneous species was formed on the electrode surface which was found to be stable and operate at turnover frequencies (TOF) of up to 25,900 s⁻¹ or 366,000 s⁻¹ cm⁻². Kinetic isotope effect (KIE) and Tafel analysis suggest rate-limiting proton coupled electron transfer (PCET) likely facilitated by the pendant amines which enabled high TOF despite evidence of redox-mediated outer-sphere electron transfer. Ni(DPMDA) was evaluated for electrocatalytic hydrogen evolution in the presence of a weaker proton donor, triethylammonium tetrafluoroborate. Under catalytic conditions, a heterogeneous species was similarly formed. Experimental evidence suggested that the identity of this species differed from that formed in the presence of anilinium as evidenced the absence of redox features attributable to the heterogeneous species, peak potential dependence on bulk catalyst concentration, and lower overpotential despite the use of a weaker proton donor. The lack of features attributable to the heterogeneous species indicated inner-sphere electron transfer and TOF of 5,700 s⁻¹ or 80,000 s⁻¹cm⁻² were observed. Similarly, KIE and Tafel analysis suggest rate-limiting PCET for which the pendant groups were implicated as hydrogen bond acceptors/donors during buffered solution studies.
Keywords: Electrochemistry; Coordination chemistry